Short-course antimicrobial therapy for paediatric respiratory infections (SAFER): study protocol for a randomized controlled trial - Pernica, Jeffrey; Harman, Stuart; Kam, April; Bailey, Jacob; Carciumaru, Redjana; Khan, Sarah; Fulford, Martha; Thabane, Lehana; Slinger, Robert; Main, Cheryl; Smieja, Marek; Loeb, Mark (Université d'Ottawa | University of Ottawa, 2018)
Abstract Background Community-acquired pneumonia (CAP) is commonly diagnosed in children. The Infectious Disease Society of America guidelines recommend 10 days of high-dose amoxicillin for the treatment of non-severe CAP but 5-day “short course” therapy may be just as effective. Randomized trials in adults have already demonstrated non-inferiority of 5-day short-course treatment for adults hospitalized with severe CAP and for adults with mild CAP treated as outpatients. Minimizing exposure to antimicrobials is desirable to avoid harms including diarrhoea, rashes, severe allergic reactions, increased circulating antimicrobial resistance, and microbiome disruption. Methods The objective of this multicentre, randomized, non-inferiority, controlled trial is to investigate whether 5 days of high-dose amoxicillin is associated with lower rates of clinical cure 14–21 days later as compared to 10 days of high-dose amoxicillin, the reference standard. Recruitment and enrolment will occur in the emergency departments of McMaster Children’s Hospital and the Children’s Hospital of Eastern Ontario. All children in the study will receive 5 days of amoxicillin after which point they will receive either 5 days of a different formulation of amoxicillin or a placebo. Assuming a clinical failure rate of 5% in the reference arm, a non-inferiority margin of 7.5%, one-sided alpha set at 0.025 and power of 0.80, 270 participants will be required. Participants from a previous feasibility study (n = 60) will be rolled over into the current study. We will be performing multiplex respiratory virus molecular testing, quantification of nasopharyngeal pneumococcal genomic loads, salivary inflammatory marker testing, and faecal microbiome profiling on participants. Discussion This is a pragmatic study seeking to provide high-quality evidence for front-line physicians evaluating children presenting with mild CAP in North American emergency departments in the post-13-valent pneumococcal, conjugate vaccine era. High-quality evidence supporting the non-inferiority of short-course therapy for non-severe paediatric CAP should be generated prior to making changes to established guidelines. Trial registration ClinicalTrials.gov, NCT02380352 . Registered on 2 March 2015.